Conceptual modelling of the factors affecting parental acceptance of silver diamine fluoride - Burak Buldur; Yasemin Yıldız (BMC Oral Health)
Abstract Background It is important to delineate how different factors relate to parental acceptance of silver diamine fluoride (SDF). Aim To develop and validate a conceptual model evaluating the factors affecting parental acceptance of SDF. Design Data were collected from 414 preschool children and their parents, and a path model was created to analyse the associations between variables affecting parental acceptability of SDF. The model comprised endogenous and exogenous variables from both parents and children. The psychometric evaluation of a Turkish version of the Parental Perceptions of Silver Diamine Fluoride Dental Colour Changes Questionnaire was also conducted. Results Parental and child oral health behaviours and the psychosocial impact of dental aesthetics had the greatest indirect effect on parental acceptability of SDF. There were significant associations between parental education level and socioeconomic status, parental socioeconomic status and oral health literacy, parental and children’s oral health behaviours, children’s oral health behaviours and oral health-related quality of life (OHRQoL), and the psychosocial effects of dental aesthetics and OHRQoL. Conclusions This study demonstrated a valid pathway of association between parental and child-related factors and parental acceptance of SDF. Furthermore, the Turkish version of the questionnaire was shown to be both reliable and valid for use.